PENEGAKAN HUKUM TERHADAP PEREDARAN ROKOK ILEGAL BERPITA CUKAI PALSU: PROBLEMATIKA DAN TANTANGAN DI SAMARINDA - Dina Anggraini; La Syarifuddin; Sofwan Rizko Ramadoni (Jurnal Ilmiah Advokasi, 2026)
The circulation of illegal cigarettes with counterfeit excise stamps constitutes a serious violation in the excise sector, causing significant losses to state revenue and creating unfair competition within the tobacco industry. While previous studies have predominantly focused on illicit cigarettes without excise stamps, limited attention has been given to cases involving counterfeit excise stamps, highlighting the need for further examination. This study aims to analyze law enforcement against the circulation of illegal cigarettes with counterfeit excise stamps and to identify the challenges and obstacles encountered in practice in Samarinda. The research employs an empirical approach using a socio-legal method, with data collected through interviews, observations, and literature review. The findings reveal that law enforcement efforts against illegal cigarettes with counterfeit excise stamps in Samarinda remain ineffective. This is influenced by several factors, including regulatory weaknesses, limited capacity of law enforcement agencies, inadequate facilities, and low public legal awareness. As a result, the circulation of illegal cigarettes continues to persist. This study highlights the need to strengthen inter-agency coordination, enhance the capacity of law enforcement authorities, and optimize monitoring mechanisms to effectively combat illegal cigarette distribution and ensure legal certainty in the excise sector.Keywords: Law Enforcement, Illegal Cigarettes, Counterfeit Excise Stamps, Excise Law